Tourism Policy for Sustainable Mountain Tourism: A Systematic Literature Review - Dhungana, Bharat Ram (Journal of Tourism and Himalayan Adventures, 2024)
The tourism sector is a key driver of socio-economic advancement. This study aims to assess tourism policy for sustainable mountain tourism using a systematic literature review. The research is based on a review of empirical studies, reports, and policy documents. The Google Scholar search engine was applied using the keywords "tourism policy" and "sustainable mountain tourism". All papers that were published from January 2010 to February 2024 have been checked for the study and 27 research papers were selected for this study using the PRISMA framework. An increased emphasis on sustainability and responsible practices has resulted in a paradigm change in the global tourism business. Sustainable tourism promotes ecological sustainability, economic viability, and social equality by mitigating the negative effects of tourism on the environment, society, and economy. Collaboration with stakeholders is essential for implementing integrated sustainable mountain tourism policies. For this, government strategies should be directed toward improving sustainability awareness, strengthening local communities and political leaders’ participation, and adopting new technologies and renewable energy sources for sustained growth.